The Role Of Usfulness In Mediation The Effect Of Arqument Quality And Popular Post In Social Media Marketing On Tendency To Give Like Symbol And Share The Content - Ita Prihatining Wilujeng; Handri Dian Wahyudi; Adela Shabrina Prameka (Publisher Cv. Inara, 2021)
Easy access to the internet provides opportunities and makes it easier to carry out business functions. The use of social media is one of the important marketing tools, messages in social media can change user attitudes and trigger consumer interaction. This study looks at the effect of argument quality and posts popularity on consumer tendencies to like and share information on social media related to a product or service mediated by usefulness. The responses of 300 respondents were analysed using PLS, the results showed that argument quality and post popularity had an influence on giving like symbols and share intentions on their social media.